Sense of Parenting Efficacy, Perceived Family Interactions, and Parenting Stress Among Mothers of Children With Autistic Spectrum Disorders - Chen, Yirong; Cheng, Tianyi; Lv, Fangyan (Frontiers in Psychology, 2022)
This study examined the relationship between maternal sense of parenting efficacy and parental stress in autistic children and the moderating effect of family interaction. A total of 263 mothers of autistic children were investigated with the Parenting Ability Scale, Family Interaction Scale and Parental Stress scale. The results showed that :(1) maternal sense of parenting efficacy significantly predicted parental stress in autistic children; (2) family interaction significantly moderated the relationship between maternal sense of parenting efficacy and parental stress in autistic children, that is, when family interaction was lower than -1.54 standard deviation, sense of parenting efficacy did not significantly predict parental stress. When family interaction was higher than -1.54 standard deviation, parenting efficacy had a significant negative predictive effect on parenting stress.